Environmental economics and policy. ( 5th ed.) (Pearson/Addison-Wesley, 2020)
Tom Tietenberg has written the ideal book for a policy-oriented course in environmental economics, accessible to both non-majors and majors. He begins with a brief introduction to the core theory, and then offers a series of self-contained policy chapters that allow professors great flexibility when planning their course. With an overhaul of the applications, a new Debate feature that highlights today’s policy issues, and the latest research integrated throughout, The Fifth Edition represents the most thorough revision in over a decade.